Clinical Utility of sFlt/PlGF Ratio in the Management of Hypertensive Disorders of Pregnancy: A Retrospective Cohort Study in a Tertiary Care Center - Gupta, Tanisha; Sharma, K. Aparna; Rana, Anubhuti; Wadhwa, Garima; Dadhwal, Vatsla (Journal of Fetal Medicine, 2024)
Hypertensive disorders of pregnancy (HDP) remain significant contributors to maternal and neonatal morbidity and mortality. These conditions arise from an imbalance between pro- and antiangiogenic factors from the placenta. The soluble fms-like tyrosine kinase-1/placental growth factor (sFlt-1/PlGF) ratio has emerged as a promising biomarker for predicting preeclampsia and its complications. This study evaluates the clinical utility of the sFlt-1/PlGF ratio in predicting adverse outcomes and guiding management.In this observational cohort study, pregnant women, either diagnosed with or at high risk for HDP, were recruited. Serum levels of sFlt-1 and PlGF were measured, and patients were classified into two groups based on a cutoff ratio of 38. Strict fetomaternal surveillance was done until delivery. Statistical analyses included comparisons of outcomes between groups and the predictive performance of the sFlt-1/PlGF ratio using receiver operating characteristic (ROC) curves.The study found that a high sFlt-1/PlGF ratio (> 38) was significantly associated with an increased likelihood of adverse fetomaternal outcomes. The high ratio group had a higher incidence of preeclampsia (75% vs. 20%, p = 0.0012), fetal growth restriction (65% vs. 5%, p = 0.0001), and a shorter enrolment and delivery period (median 13.5 vs. 23 days, p = 0.04884). ROC analysis demonstrated strong predictive performance with an area under the curve of 0.892, indicating high accuracy in identifying patients at risk for adverse outcomes.The sFlt-1/PlGF ratio effectively stratified patients into high risk and low risk categories for adverse fetomaternal outcomes. This study supports the integration of the sFlt-1/PlGF ratio into clinical practice to enhance risk assessment and decision making in managing HDP.This study highlights the clinical utility of the sFlt-1/PlGF ratio in the management of HDP. By effectively stratifying patients into high risk and low risk categories, this biomarker enables targeted surveillance and intervention, reducing unnecessary hospital admissions and improving maternal and fetal outcomes. Its integration into routine prenatal care can enhance risk assessment and optimize resource allocation, particularly in low resource settings.
Keywords: preeclampsia; hypertensive disorders of pregnancy; sFlt-1/PlGF ratio; preterm delivery; fetal growth restriction